Metal-organic framework nanopesticide carrier for accurate pesticide delivery and decrement of groundwater pollution. - Nguyen, Hoang Ly (Elsevier Ltd., 2023)
The motivation of the present study was a synthesis of the nanocomposites of UiO-66@ZnO/Biochar to embed carbendazim (CBZ) pesticide inside its porous structures for smart spraying and cleaner production. CBZ@UiO-66@ZnO/Biochar had the purpose of not only smart spraying to avoid releasing a large amount of CBZ into the groundwater but also of accurately delivering the CBZ pesticide to the desired grass/plant. High-resolution electron microscopy was introduced to characterise the morphologies of prepared composites with spatial elemental distribution mapping. X-ray diffraction (XRD) patterns and micro-Raman spectroscopy were employed for the crystal structures of UiO-66@ZnO. Spectral UV–Vis and Fourier transform-infrared (FT-IR) tools were utilized to estimate the UiO-66@ZnO/Biochar-based adsorption and release of CBZ into the dimethyl sulfoxide (DMSO)-water mixture. Our results indicated that the adsorption capacities of CBZ into the DMSO-water mixture onto UiO-66@ZnO and UiO-66@ZnO/Biochar nanocomposites were obtained at 68.8% and 72.6%. The half-life of photodegradation rate constants for CBZ@UiO-66@ZnO/Biochar was found to be 12.3 times longer than that of free CBZ. Notably, CBZ@UiO-66@ZnO/Biochar inhibitory concentration 50% (IC50) determination was estimated at 73.8 μg/L and 209 μg/L for Fusarium oxysporum and Aspergillus niger. This work provides a comprehensive experimental scheme for the chemisorption process of CBZ onto the UiO-66@ZnO/Biochar composite materials and the nanopesticide applications in sustainable agriculture towards cleaner productions.